Challenges in diagnosis and treatment of cushing disease in a 12-year-old boy. Case report - Agim Gjikopulli; Sonila Tomori; Marjeta Tanka; Donjeta Bali (La Pediatria Medica e Chirurgica, 2025)
Cushing’s Disease (CD), defined as hypercortisolism caused by excess Adrenocorticotropic Hormone (ACTH) secretion by a pituitary corticotroph adenoma, rarely presents in the pediatric age range. The aim is to describe a 12-year-old Albanian boy with a challenging pathway to diagnosis and treatment process for Cushing's disease. He presented with headaches, rapid weight gain during the last three years, stunting, increased body hair growth, and a typical Cushingoid appearance. After a consultation in the Pediatric Endocrinology Unit at the University Hospital Center, “Mother Teresa,” in Tirana, the boy was pre-diagnosed with Cushing Syndrome, and hypophyseal adenoma was suspected due to suggestive laboratory tests, although non-consistent imaging results. An ectopic ACTH-dependent Cushing syndrome was suspected together with neuroendocrine neoplasia (carcinoid tumor) as a thoracic CT showed a nodular lesion with regular-lobulated sharp contours in the lower lobe of the right lobe resulted in pulmonary tuberculosis granuloma. Even imaging failed to identify the ACTHsecreting microadenoma; the decisive examination was an intervention to collect samples from the inferior petrosal sinus during the CRH test, which found a left-side ACTH-secreting focus. Left hemi-hypophysectomy was performed using gamma knife therapy, resulting in effective normalization of hypercortisolism, but with the side effect of growth hormone deficiency.